EXPLORING INVISIBLE HORIZONS: THE POTENTIAL OF VIRTUAL REALITY TECHNOLOGY IN CHEMISTRY EDUCATION - Yulchiyeva Oysara Yandashevna (American Journals, 2023)
Virtual reality (VR) technology has experienced significant progress in recent years, and its applications have spread to various fields. This article explores the potential benefits and challenges of integrating VR technology into chemistry learning. Through a comprehensive review of current research, this paper demonstrates how VR can improve chemistry education by offering an immersive, experiential learning experience, increasing student engagement, promoting conceptual understanding, and minimizing laboratory costs. In addition, we discuss potential future developments in the field and explore the challenges that need to be addressed to fully harness the power of VR in chemistry education.